Indo-Pacific : One Region, Many Visions? - Chaturvedy, Rajeev Ranjan (2019)
Diverse perspectives on the idea of “Indo-Pacific” are resulting in a lack of clarity on this concept. As a framework, the Indo-Pacific seeks to create a connected multipolar Asia that must be governed by commonly agreed international norms, rules and practices. But what is the Indo-Pacific?